Evaluation of enterprise’s competitive position – case study - Chrobocińska, Katarzyna (Ocena pozycji konkurencyjnej przedsiębiorstwa – studium przypadku, 2020)
One of the dimensions of the competitiveness of an enterprise is the competitive position, which relates to competitive advantage, and often results from the competitive potential and skillfully applied instruments of competing. There are many ways enabling the evaluation of competitive position, which, among others, include a financial analysis. The main goal of a financial analysis in an enterprise is to evaluate the financial condition of the entity, which consequently allows to indicate deficiencies and strengths of the subject and the potential threats. The aim of this research paper was an attempt to evaluate the competitive position of one of the largest producers of poultry products in Poland – Indykpol S.A. – using the ratio analysis. This elaboration also applied the case study method to illustrate the situa-tion of Indykpol S.A. The analysis of the behaviour of various financial ratios led to a conclusion that the competitive position of Indykpol in its industry was relatively strong and quite stable. Moreover, during the survey period, the overall level of liabilities suggests that all the obligations are covered by a sufficient amount of assets at the firm’s disposal. The level of the financial results in 2018 allowed to make a positive evaluation of the company’s growth perspective, and coincided with the market launch of a new and higher quality product line – “Samo Dobro” – which contributed to an increase in the profit generation potential
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 20-30
Keywords: competitive position; ratio analysis; production of poultry products; pozycja konkurencyjna; analiza wskaźnikowa; ocena pozycji konkurencyjnej